VD_FINDINFO HC / 2012 / 102 vom 30. Januar 2012 - VD Tribunal cantonal (2012)
SIMULATION, COMPENSATION DE CRÉANCES, MANDAT | 120 CO, 18 CO, 400 CO, 308 CPC (CH), 310 CPC (CH), 312 al. 1 CPC (CH), 317 CPC (CH)